A Low Cost C8051F006 SoC-Based Quasi-Static C-V Meter for Characterizing Semiconductor Devices - Endah Rahmawati; Riska Ekawita; Maman Budiman; Mikrajuddin Abdullah; Khairurrijal Khairurrijal (Universitas Ahmad Dahlan, 2012)
Based on a C8051F006 SoC (system on-a-chip), a simple and low cost quasi-static capacitance-voltage (C-V) meter was designed and developed to obtain C-V characteristics of semiconductor devices. The developed C-V meter consists of a capacitance meter, a programmable voltage source, a C8051F006 SoC-based slave controller, and a personal computer (PC) as a master controller. The communication between the master and slave controllers is facilitated by the RS 232 serial communication. The accuracy of the C-V meter was guaranteed by the calibration functions, which are employed by the program in the PC and obtained through the calibration processes of analog to digital converter (ADC), digital to analog converters (DACs) of the C8051F006 SoC, and the programmable voltage source. Examining 33-pF and 1000-pF capacitors as well three different p-n junction diodes, it was found that the capacitances of common capacitors are in the range of specified values and typical C-V curves of p-n junction diodes are achieved.